Geometrically nonlinear large deformation analysis of triangular CNT-reinforced composite plates. (November 2016) - Zhang, L.W.; Liu, W.H.; Liew, K.M.
Abstract: A first known investigation on the geometrically nonlinear large deformation behavior of triangular carbon nanotube (CNT) reinforced functionally graded composite plates under transversely distributed loads is investigated. The analysis is carried out using the element-free IMLS-Ritz method. In this study, the first-order shear deformation theory (FSDT) and von Kármán assumption are employed to account for transverse shear strains, rotary inertia and moderate rotations. A convergence study is conducted by varying the supporting size and number of nodes. The effects of transverse shear deformation, CNT distribution and CNT volume fraction on the nonlinear bending characteristics under different boundary conditions are examined. Highlights: Nonlinear analysis of triangular CNT-reinforced composite plates is considered. The plate considered is under different boundary conditions. The element-free IMLS-Ritz method is employed for the analysis. The effect CNT distributions on the large deformation behavior is examined.